Comparative Study of HPLC Detectors in PT. FIP : A Review - Annisa Luthfiyah Handini; Patihul Husni; Indriana Agustin Claradila Frinda (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
High Performance Liquid Chromatography (HPLC) is a vital analytical technique used for separation, identification, and quantification of compounds in complex mixtures. This review explores the comparative performance of four detectors employed in the Chemical Laboratory of PT FIP: UV-Visible, Refractive Index (RI), Conductivity, and Evaporative Light Scattering Detector (ELSD). Each detector operates on distinct principles and is selected based on analyte characteristics such as the presence of chromophores, ionic nature, or volatility. The UV-Vis detector remains the most widely used due to its precision and compatibility with chromophoric compounds. However RI, Conductivity, and ELSD detectors serve as essential alternatives for analytes that lack UV absorption, non-ionizing, or exhibit low volatility. This review summarizes the key principles, advantages, limitations, and applications of each detector. The comparative evaluation highlights the strengths and constraints of each system, facilitating method optimization in pharmaceutical analysis.